Studie logistických služeb pro konkurenční výhodu - Pavlas, Vladimír (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Diplomová práce analyzuje podnikání a logistické služby obchodní společnosti, popisuje teoretické přístupy k optimalizaci služeb a navrhuje zlepšení pro získání konkurenční výhody.

Master‘s Thesis analyze business and logistic services of trading company, describe theoretic accesses to services optimalization and propose innovations for purchasing of competitive advantage.
The Study of Logistic Services for Competitive Advantage
Keywords: Doprava; konkurence; logistika; služby.; Transit; competition; logistics; services.